2006
DOI: 10.1002/bies.20374
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of genomic rearrangements and gene expression changes in plant polyploids

Abstract: SummaryPolyploidy is produced by multiplication of a single genome (autopolyploid) or combination of two or more divergent genomes (allopolyploid). The available data obtained from the study of synthetic (newly created or human-made) plant allopolyploids have documented dynamic and stochastic changes in genomic organization and gene expression, including sequence elimination, inter-chromosomal exchanges, cytosine methylation, gene repression, novel activation, genetic dominance, subfunctionalization and transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
325
3
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(356 citation statements)
references
References 114 publications
(166 reference statements)
7
325
3
13
Order By: Relevance
“…In development, duplicate genes diverge in expression relatively slowly and tend to be coregulated. A relatively slow rate of expression divergence between the duplicates might provide genetic robustness against null mutations [10] and selective advantage by dosage-dependent gene regulation [11,29] that enables organisms to fine-tune complex regulatory networks through genetic and epigenetic mechanisms [30]. Therefore, duplicate genes could promote an adaptive mechanism for environmental changes or provide genetic robustness and dosage-dependent regulation during organismal development, which might facilitate polyploid evolution.…”
Section: Resultsmentioning
confidence: 99%
“…In development, duplicate genes diverge in expression relatively slowly and tend to be coregulated. A relatively slow rate of expression divergence between the duplicates might provide genetic robustness against null mutations [10] and selective advantage by dosage-dependent gene regulation [11,29] that enables organisms to fine-tune complex regulatory networks through genetic and epigenetic mechanisms [30]. Therefore, duplicate genes could promote an adaptive mechanism for environmental changes or provide genetic robustness and dosage-dependent regulation during organismal development, which might facilitate polyploid evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Recent polyploids have been identified in fishes and amphibians (Choleva and Janko, 2013;Gui and Zhou, 2010;Otto, 2007;Song et al, 2012) and some diploidized tetraploid species have been demonstrated in some teleost fish lineages including cyprinids, catostomids, and salmonids (Allendorf and Thorgaard, 1984;Collares-Pereira et al, 2013;Gui and Zhou, 2010;Yang and Gui, 2004), but the two recent rounds of polyploidy have been documented only in the polyploid gibel carp. Recent genome-wide studies have confirmed that the problem of genetic incompatibility raised by polyploidy may be resolved by the accumulation of diverse mutational changes to form a stable chimerical and diploidized genome (Buggs et al, 2011;Chen and Ni, 2006;Louis et al, 2012;Tate et al, 2009). And, a lot of biogeographic and ecological investigations have revealed the close association between polyploidy occurrence and environmental change (Parisod et al, 2010;Wu et al, 2010).…”
Section: Evolutionary Consequences Of Polyploidy In Gibel Carpmentioning
confidence: 99%
“…It has also been reported that genome polyploidation can have potential selective advantages such as increased heterozygosity, as well as novel variation and allelic subfunctionalization [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms that contribute to the novel phenotypes of autopolyploidy plants remain largely unexplored [48][49][50][51]. Interestingly, one report has described the loss of selfincompatibility after polyploidation events [52].…”
Section: Discussionmentioning
confidence: 99%